2015
DOI: 10.1073/pnas.1420792112
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent sequestration of RVE8 by LNK proteins shapes the diurnal oscillation of anthocyanin biosynthesis

Abstract: Circadian clocks sustain 24-h rhythms in physiology and metabolism that are synchronized with the day/night cycle. In plants, the regulatory network responsible for the generation of rhythms has been broadly investigated over the past years. However, little is known about the intersecting pathways that link the environmental signals with rhythms in cellular metabolism. Here, we examine the role of the circadian components REVEILLE8/LHY-CCA1-LIKE5 (RVE8/LCL5) and NIGHT LIGHT-INDUCIBLE AND CLOCK-REGU-LATED genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 28 publications
(36 reference statements)
3
76
0
1
Order By: Relevance
“…Its function is partially dependent on LNKs ; however, it remains unknown how LNKs act as co-activators due to the lack of functional domains. Intriguingly, LNKs can also bind to CCA1 and LHY , and LNKs act as repressors for anthocyanin biosynthesis genes and work antagonistically with RVE8 (Pérez-García et al, 2015). Given that LNKs act downstream of phyB signaling (Rugnone et al, 2013), LNKs also have roles in the light signaling pathway.…”
Section: A Molecular Framework Of the Circadian Oscillatormentioning
confidence: 99%
“…Its function is partially dependent on LNKs ; however, it remains unknown how LNKs act as co-activators due to the lack of functional domains. Intriguingly, LNKs can also bind to CCA1 and LHY , and LNKs act as repressors for anthocyanin biosynthesis genes and work antagonistically with RVE8 (Pérez-García et al, 2015). Given that LNKs act downstream of phyB signaling (Rugnone et al, 2013), LNKs also have roles in the light signaling pathway.…”
Section: A Molecular Framework Of the Circadian Oscillatormentioning
confidence: 99%
“…Another small family of morning-expressed genes that plays an important role in the circadian oscillator is comprised by the NIGHT LIGHT-INDUCIBLE AND CLOCK-REGULATED (LNK1, 2, 3, and 4) components (Rugnone et al 2013). LNKs interact with the RVEs and have been shown to be able to either antagonize or coactivate RVE8 (Xie et al 2014;Pérez-García et al 2015).…”
Section: Clock Organization In Arabidopsis Thalianamentioning
confidence: 99%
“…32 Currently, a study has revealed that 2 circadian components NIGHT LIGHT-INDUCIBLE AND CLOCK-REGULATED (LNK) and RVE8 collaborate to control the anthocyanin metabolic pathway. 33 The MYB-related transcription factor RVE8 can bind directly to the promoter of TIMING OF CAB EXPRESSION1 (TOC1) and facilitate this gene expression by increasing the acetylation level of histone H3, whereas CCA1 inhibits TOC1 expression via the reduction of the histone acetylation level. 34 In addition, the study by Perez-Garcia et al 33 revealed that RVE8 can directly associate with the promoters of genes involved in anthocyanin biosynthesis and regulate the expressions of these genes in response to diurnal oscillations.…”
mentioning
confidence: 99%
“…33 The MYB-related transcription factor RVE8 can bind directly to the promoter of TIMING OF CAB EXPRESSION1 (TOC1) and facilitate this gene expression by increasing the acetylation level of histone H3, whereas CCA1 inhibits TOC1 expression via the reduction of the histone acetylation level. 34 In addition, the study by Perez-Garcia et al 33 revealed that RVE8 can directly associate with the promoters of genes involved in anthocyanin biosynthesis and regulate the expressions of these genes in response to diurnal oscillations. From these findings, RVE8 can be considered a circadianrelated regulator of anthocyanin biosynthesis in plants.…”
mentioning
confidence: 99%